0606 Comparative Effectiveness of Sleep Apnea Screening Tools During Inpatient Rehabilitation for Moderate to Severe TBI. (27th May 2020) - Richardson, R; Schwartz, D; Drasher-Phillips, L; Ketchum, J; Calero, K; Dahdah, M; Monden, K; Bell, K; Hoffman, J; Magalang, U; Bogner, J; Whyte, J; et al.
Abstract: Introduction: Recent studies highlight prevalent obstructive sleep apnea after moderate to severe TBI during a time of critical neural repair. The purpose of this study is to determine the diagnostic sensitivity, specificity and comparative effectiveness of traditional sleep apnea screening tools in TBI neurorehabilitation admissions. Methods: This is a prospective diagnostic comparative effectiveness trial of sleep apnea screening tools (STOPBANG, Berlin, MAPI [Multi-Apnea Prediction Index]) relative Level 1 polysomnography at six TBI Model System Inpatient Rehabilitation Centers. Between 05/2017 and 02/2019, 449 of 896 screened were eligible for the trial with 345 consented (77% consented). Additional screening left 263 eligible for and completing polysomnography with final analyses completed on 248. The primary outcome was the Area Under the Curve (AUC) of screening tools relative to total apnea hypopnea index ≥15 (AHI, moderate to severe apnea) measured at a median of 47 days post-TBI (IQR 29-47). Results: Participants were primarily young to middle age (AGE IQR 28, 40, 59), male (81%), white (74%), and had primarily severe TBI (IQR GCS 3, 6, 14). A subset (26%) had a history of military service. Results revealed that the Berlin high risk score (ROC-AUC=0.63) was inferior to the MAPI (ROC-AUC = 0.7802) (p=.0211, CI: 0.0181, 0.2233) and STOPBANG (ROCAUC = 0.7852) (p=.0006, CI: 0.0629, 0.2302); both of which had comparable AUC (p=.7245, CI: -0.0472, 0.0678). Findings were similar for AHI≥30 (severe apnea); however, no differences across scales was observed at AHI>5. The pattern was similar across TBI severity subgroups except for delirium or post-traumatic amnesia status wherein the MAPI outperformed the Berlin and STOPBANG. Youden's Index to determine risk yielded lower sensitivities but higher specificities relative to non-TBI samples. Conclusion: This study is the first to provide clinicians with data to support a choice for which sleep apnea screening tools are more effective during inpatient rehabilitation for moderate to severe TBI (STOPBANG, MAPI vs Berlin) to help reduce comorbidity and possibly improve neurologic outcome. Support: PCORI (CER-1511-33005), GDHS (W91YTZ-13-C-0015; HT0014-19-C-0004)) for DVBIC, NIDILRR (NSDC Grant # 90DPTB00070, #90DP0084, 90DPTB0013-01-00, 90DPTB0008, 90DPT80004-02).